A lei da “ficha limpa” à luz da democracia deliberativa - Tinôco, Karine Martins Fernandes (2017)
The general goal of this work was to comprehend the democratic process that resulted in the Brazilian Complimentary Law 135/2010, also known as the "Clean Record Law", from three different moments: the discussion as a relevant theme in the life-world (Lebenswelt), within the anti-corruption public sphere; the manufacturing of the Bill in the political system; and the results of the actual application of the mentioned law. The study deals specifically with the origins and the formation of the anti-corruption public sphere, the prevailing arguments within the National Congress, regarding the procedure of manufacturing the Bill and the results of the Clean Record Law, from Habermas' deliberative policy perspective, using examples of real facts occurred in Minas Gerais State - Brazil. In order to understand this process, political corruption was analyzed in Brazil. The theoretical framework contains Habermas´ concepts of political rights, public sphere, life-world and systems. The information was collected through official documents, web pages, reports and social networks, and systematized based on the Critical Hermeneutics approach. The following analytical categories were addressed: political rights, facticity and validity, public sphere, public deliberation, political culture, civil society, political decisions and participation of the judiciary. The results show that an anti-corruption public sphere was formed through the mobilization of civil society in Brazil, triggered by corruption scandals, lack of adequate legislation and punishment, non-recovery of diverted public funds, etc.. Citizens exercised their popular sovereignty by proposing, in use of a legitimate democratic instrument - the popular Bill initiative - the "Clean Record” Bill. In the Project´s proceduring in Congress, the main results demonstrate that, despite all the divergences and difficulties for its approval, the Bill did get approved, but only because of the strong influence of the "life-world". Regarding the application of the Clean Record Law, the results indicated the discussions on the constitutionality of the law and its application to the 2010 elections, together with the results obtained by the analysis of the application on the rejected candidatures, highlight the validity and legitimacy of this Law, which has effects in the life-world and in the systems, according with the public opinion and strong will of its authors (the people). It should also be noted that the validity and legitimacy of a given law, according to Habermas, does not depend on the success of its applications alone, but its procedures must always be considered. Finally, this work showed that Complementary Law 135/2010 (Clean Record Law) is the fruit of the protagonism of civil society in Brazil, and an example of the applicability of social management when observing the dialogic management action, focused on the public interest and in the construction of the common wealth.